COVID-19 Strikes U.S. Higher Education - Raquel Wright-Mair; Candice Peters; Gabrielle A. McAllaster (Journal of Postsecondary Student Success, 2021)
International students have contributed to the internationalization and diversification of U.S. higher education; yet, when COVID-19 (i.e., coronavirus) struck, it became evident that this subset of the U.S. higher education student population was left unaccounted for and unprotected. This manuscript underscores the unimaginable damage and disruption that can occur when a global crisis of the highest magnitude meets under preparedness, pre-existing discrimination, and impulsive policy-making. It also highlights, for context, past crises and their impacts on international students, thus establishing a trend which places international students at the epicenter of the blow’s concomitant with crises of different nature. Moreover, the manuscript provides considerations higher education stakeholders should reflect upon, as well as the following implications for higher education institutions: a) Establish support systems, b) create a sustainable emergency/crisis relief fund, c) seek and maintain non-local partnerships, d) get in good trouble, and e) develop intervention programs. In enacting these tangible solutions, institutions would be able to guide, serve, and support international students more effectively during and after crises.